PENGARUH KUALITAS KANTOR AKUNTAN PUBLIK (KAP) DAN KARAKTERISTIK KOMITE AUDIT DAN KARAKTERISTIK KOMITE AUDIT TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2016-2019) - Anigo Trikartiko; Totok Dewayanto (Diponegoro Journal of Accounting, 2021)
The aim of this study is to examine the role of audit specialization, audit fees, independency audit committee, and board-gender diversity audit committee on tax avoidance. This study uses firm size as a control variable.       The population in this study consists of manufacturing companies in Indonesia Stock Exchange for the period 2016 - 2019. Sample determined with purposive sampling method. Total sample of this research are 200 companies.            This study used multiple regression analysis for hypotheses testing. The results of this study shows that audit specialization, independency audit committee, and board-gender diversity audit committee has positive and significant effect on less tax avoidance. This study also shown that audit fees has positive but insignificant effect on less tax avoidance.